Personal and organizational transformation towards sustainability : walking a twin-path - Ernst, Dorothea. (Principles for responsible management education collection., 2016)
Leading change towards sustainable development. Inspired by the WBCSD Vision 2050 in which "all people live well within the limits of the planet", this books asks how do we achieve this bold ambition? Telling a story of personal growth and corporate transformation, it provides insights and tools for anyone driving sustainable development within their organizations and in their own lives. Discover how you can consciously use your professional role as a source of change. Learn how the consistent use of few, yet meaningful visuals, enables generative dialogue and communication for aligned problem solving within multi-disciplinary and multi-stakeholder teams. See how personal mastery can guide you in identifying the contribution you can make, both towards wider goals and your individual well-being. On this journey, "meaning-making" is essential. In organizations, co-creation of a shared language and an understanding of disruptive innovation are fundamental to successful transformation. In exploring these topics, the book builds on a set of core concepts: Rogers' innovation diffusion curve, the triple bottom line (people, profit, planet) expanded with a fourth "P" (the individual), and the WWF "ice-breaker" graph which maps the environmental footprint against the human development index.